MANUSIA SEBAGAI MAKHLUK PEDAGOGIS DALAM FILSAFAT PENDIDIKAN ISLAM - Mohammad Wira Yudha; Mohammad Ahyan Yusuf Sya'bani (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Humans in Islam have the potential to be educated as well as educate or pedagogically, talent and their environment are two lines of convergence that strive for human development, besides that as beings who can develop and be educated, humans also need education to develop themselves. Because humans in essence have the ability to know the highest level, as well as placing them as individual, social and cultural creatures that grow and develop in culture as a whole, including education and also as humans have rational abilities, from rational abilities that humans can learn from what they see. This study wants to reveal how the concept of humans as pedagogical beings in Islamic educational philosophy?. The method used is qualitative with a library research approach. The result of this research is that humans as pedagogical creatures in Islam have good potentials to be developed in education. Both himself as an educator (subject) and as a learner (object). Because humans were created by Allah as noble and perfect creatures compared to other creatures.